The Effect of Excise Burden, Income Smoothing, and Effective Tax Rate (ETR) on Financial Performance - Saffanah, Nurina; Pratama, Vanny Arsamba (Manunggal Halim Jaya, 2025)
The tobacco industry is a strategic sector the significantly contributes to national revenue through excise and taxation. However, high fiscal burdens may suppress the financial performance of companies operating in this sector. This study aims to examine the effect of excise burden, income smoothing practices, and effective tax rate (ETR) on the financial performance of tobacco companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach as employed using multiple linear regression analysis. The data were obtained from secondary sources, namely annual reports of four tobacco companies over the period of 2021 to 2023, resulting in a total of 12 observations (N=12). The results indicate that excise burden has a significant negative effect on Return on Assets (ROA), income smoothing has a significant positive effect on ROA, and ETR also has a significant negative effect on ROA. These findings suggest that fiscal pressure from excise and taxation needs to be counterbalanced by adaptive managerial strategies, such as cost efficiency and healthy earnings management. The results align with cost theory, signaling theory, and agency theory. In conclusion, internal fiscal management plays a critical role in maintaining profitability under increasingly strict government regulations. Companies are advised to enhance cost control and tax planning as mitigation strategies against fiscal burdens. The practical implication of this study is to provide insights for corporate management and policymakers on the importance of balancing fiscal policy and industry competitiveness.